New Method of Inversion Vertical Electrical Logging (IVEL) for Identification of Coal Seam Prospect of Muara Enim Regency, South Sumatera - Ibrahim, Eddy; D.H, Endang Wiwik; Sutopo, (International Journal of Natural Sciences Research, 2016)
The Measurement Inversion Vertical Electrical Logging (IVEL) in the Regency of Muara Enim Indonesia aims at measuring and mapping the resistivity associated with the spread of lithologi coal seam as Coal Bed Methane reservoirs (CBM). Resistivity measurements of new method performed with the sounding system as much as 5 points, with spaces between the point of 100-200 m, range of penetration achieved with these measurements to a depth of 500 m from the ground surface. The results of the processing and interpretation of data from the IVEL indicate that on site research was generally dominated by layers of rock and clay shale with a resistivity less than 2 Ohm.m as well as sandstones 2-5 Ohm.m. while the coal layer was found at the depth of 60 to 80 meters,100 to 180 meters, and 340 to 350 meters above the resistivity value of 5 Ohm.m.